2018
DOI: 10.1093/geroni/igy036
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Orientation and Gender Differences in Aging Perceptions and Concerns Among Older Adults

Abstract: Background and Objectives Ageism (negative attitudes and behavior toward older adults) is a serious social issue and is of growing concern as the population of older adults continues to increase. Research demonstrates that negative aging perceptions and aging concerns are associated with poor health and well-being among older adults; yet, few studies have examined sexual orientation or gender differences in aging perceptions and concerns among older adults. Research Design and Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0
4

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 48 publications
1
27
0
4
Order By: Relevance
“…Subjective Cognitive Decline-The question on SCD asked "During the past 12 months, have you experienced confusion or memory loss that is happening more often or is getting worse?" This question elicited a binary response (yes vs. no) and has been used in previous studies examining SCD [32,36].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Subjective Cognitive Decline-The question on SCD asked "During the past 12 months, have you experienced confusion or memory loss that is happening more often or is getting worse?" This question elicited a binary response (yes vs. no) and has been used in previous studies examining SCD [32,36].…”
Section: Methodsmentioning
confidence: 99%
“…Potential Confounders-A confounder was considered in the current study if it was associated with SGM and an independent risk factor for SCD but was not in the pathway between SGM and SCD. Based on literature review a priori [17,[35][36][37][38][39][40][41], confounders considered included: age (60-69, 70-79, 80-80 vs. 45-59), income ($15,000-<$50,000, ≥ $50,000 vs. <$15,000), education (high school graduate, > high school graduate vs. < high school graduate), and race/ethnicity (Black, Non-Hispanic; Other, Non-Hispanic, Hispanic vs. White, non-Hispanic). (From this point forward, when referring to Black, Other, and White races, we are referring to non-Hispanic ethnicity).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These experiences increase levels of stress among these populations and may contribute to poor sleep levels, increased anxiety and other mental health concerns. For example, in a recent study it was found that among sexual minority participants, discrimination based on age and sexual orientation predicted greater levels of mental health concerns (Lytle, Apriceno, Dyar, & Levy, 2018). Secondly, sexual minorities, at least in the case for nonmonogamous men who have sex with men, are disproportionally impacted by HIV, which in itself is a risk factor for cognitive impairment and dementia (Heaton et al, 2011;Rourke, Halman, & Bassel, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Although current evidence on sex differences in SA is inconclusive (Kornadt et al, 2013;Levy et al, 2002;Schafer & Shippee, 2010), the distinct attributional processes, social roles, and age-related expectations that characterise men and women may impact on their evaluations of age-related changes and consequently on SA (Barrett, 2005;Hvas, 2006;Settersten, 2017). Those studies reporting a younger SA among women hypothesised that this is due to women having some characteristics associated with a younger SA including optimism, adaptation, resilience, strong family identity, and elongated view of the life course (Hvas, 2006;Lytle et al, 2018;Montepare, 2020;Sontag, 1997). Those studies reporting more negative SA among women instead suggested that their results are due to women being more likely than men to experience poor physical health and ageing anxiety, and to internalise negative age-related stereotypes (Barrett, 2005).…”
Section: Introductionmentioning
confidence: 99%